Manajemen Pengembangan SDM melalui Penguatan Komunitas Belajar Dalam Meningkatkan Kompetensi Pedagogik Guru - Santi Susanti; Neng Reni Rizki; Selvi Anggraeni; Ikal Ludya Hakim; Amin Abdulah; Dinny Mardiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Teachers’ pedagogical competence plays a pivotal role in determining the quality of learning processes in elementary schools. Therefore, teacher capacity development should be implemented systematically and continuously through approaches that are relevant to educational practice. This study aimed to describe the implementation of human resource development management through a learning community in enhancing teachers’ pedagogical competence at SDN 2 Palabuhanratu, Sukabumi Regency. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, field observations, and document analysis. Participants included the school principal, the coordinator of the BAKEKOK learning community, and teachers actively involved in the community. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. The findings revealed that teacher human resource development was carried out through four managerial functions: planning, organizing, implementation, and evaluation of learning community activities. The BAKEKOK learning community served as a collaborative platform where teachers shared experiences, reflected on instructional practices, and collectively addressed classroom challenges. Participation in the learning community positively influenced teachers’ pedagogical competence, particularly in lesson planning, student-centered instruction, assessment practices, and reflective teaching. The study concludes that learning communities can function as an effective strategy for sustainable educational human resource development.